Clinical heterogeneity and prognostic determinants in rheumatoid vasculitis: a systematic analysis of organ-specific manifestations, therapeutic outcomes, and biomarker correlations - Wang, Dongyi; Lu, Le; Shen, Junyi; Zhang, Yuping; Li, Muzi; Shang, Wei (Frontiers in Immunology, 2025)
BackgroundRheumatoid vasculitis (RV), a severe extra-articular complication of rheumatoid arthritis (RA), with current evidence limited to fragmented case reports and a lack of consensus on diagnostic/therapeutic protocols. This study systematically evaluated the clinical heterogeneity, prognostic determinants, and management challenges of RV through the comprehensive analysis of case reports.MethodsWe conducted a systematic review of 112 RV cases from PubMed, Scopus, and Embase in the past 10 years. After dual-reviewer screening and exclusion of confounded cases (concurrent autoimmune diseases, drug-induced vasculitis, infection-associated cases), data spanning demographics, organ involvement patterns, treatments, and outcomes were extracted. Subsequent statistical analyses and data visualization were conducted using R software.ResultsThe mortality group exhibited significantly higher rates of concurrent infections (P = 0.03) and elevated anti-cyclic citrullinated peptide (anti-CCP) antibody titers (P = 0.04) compared to the survival group. Only less than half of the medical records had histopathological confirmation of the diagnosis, which was particularly notable in cardiac (14.3%, 1/7), pulmonary (33.3%, 2/6),and cerebral (25.0%, 9/36) involvement. During the induction of disease remission, glucocorticoids remained the primary therapy. Both conventional synthetic disease-modifying antirheumatic drugs (DMARDs) (P < 0.05) and biologic DMARDs (P < 0.001) demonstrated favorable prognostic associations.ConclusionsThis study highlighted RV’s heterogeneous organ involvement and underscored the prognostic value of anti-CCP and infection screening. The limited histopathological confirmation rates emphasized the need for multimodal diagnostics. Our findings also provided robust evidence supporting the therapeutic efficacy of biologic DMARDs in RV management.